Pandemics of COVID-19 and racism: how HBCUs are coping - Komanduri S Murty; Tamara B Payne (AIMS Press, 2021)
Historically Black Colleges and Universities (HBCUs) are currently facing unique challenges to deal with parallel pandemics of COVID-19 and Racism, given the population they serve (mostly African American) are at high risk of these unprecedented crises. HBCU leaders are adopting various strategies to respond to both the pandemics in order to protect their stakeholders. This paper addresses various models that HBCUs have adopted or planned to adopt to cope with these pandemics, gleaning the data from various secondary sources and selected first-hand interviews with HBCU administrators.